Time discretization of nonlinear hyperbolic systems on networks. Issue 1 (18th November 2019) - Altmann, Robert; Zimmer, Christoph
Abstract: In view of gas networks, the simulation of hyperbolic systems on networks has recently caused large interest. We consider the case with a nonlinear damping term and a small parameter ϵ such that – in the linear case – the system turns parabolic for ϵ =0. Based on this property and an expansion in ϵ, we derive a novel time integration scheme.